Hot rolled steel plate

JP7633565B2Active Publication Date: 2025-02-20NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023543681
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-24
Filing Date
2022-04-08
Publication Date
2025-02-20
Estimated Expiration
2042-04-08

Smart Images

  • Figure 0007633565000004
    Figure 0007633565000004
  • Figure 0007633565000001
    Figure 0007633565000001
  • Figure 0007633565000002
    Figure 0007633565000002
Patent Text Reader

Abstract

Provided is a hot-rolled steel plate that has a prescribed chemical composition, the microstructure thereof being, in terms of surface area ratio, at least 70% pearlite, 0 to 30% ferrite, and 0 to 30% bainite. The perlite has, per 10 μm2, less than 10 grains of cementite having a major-axis length over 0.3 μm and an aspect ratio of less than 3.0, and has a tensile strength of at least 900 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot-rolled steel sheet, and more particularly to a hot-rolled steel sheet used for structural members of automobiles and the like, which has high strength, uniform elongation and excellent punched edge fatigue properties. [Background technology]

[0002] In recent years, the automotive industry has been seeking to reduce the weight of chassis components and other parts in order to improve fuel efficiency. In order to achieve both weight reduction and crashworthiness in parts, increasing the strength of the steel plates used is one effective method, and against this background, the development of high-strength steel plates is underway.

[0003] On the other hand, as strength increases, the uniform elongation necessary for component forming and the fatigue properties of the punched edge generally decrease. To improve uniform elongation, TRIP steels that utilize retained austenite have been devised, but in such steels, martensite with high hardness and low toughness is generated near the edge during punching due to processing-induced transformation, and the generation of such martensite can cause a decrease in the fatigue properties of the punched edge.

[0004] Patent Document 1 describes a hot-rolled steel sheet having a predetermined chemical composition, characterized in that the metal structure is, in terms of area ratio, 90-100% pearlite, 0-10% pseudo-pearlite, and 0-1% pro-eutectoid ferrite, the average lamellar spacing of the pearlite is 0.20 μm or less, and the average pearlite block diameter of the pearlite is 20.0 μm or less. Patent Document 1 also describes that the above configuration makes it possible to obtain a hot-rolled steel sheet having a high strength of tensile strength of 980 MPa or more and excellent ductility, hole expandability, and punchability.

[0005] In relation to the pearlite-based structure described in Patent Document 1, Patent Document 2 describes that in the case of a hot-rolled steel sheet, if the growth time during pearlite transformation is sufficient, it is common for the sheet to have lamellar cementite with an elongated shape. Patent Document 3 describes a hot-rolled steel sheet in which the main phase is pearlite, the remaining phase contains 20% or less of ferrite, and the lamellar spacing of the pearlite is 500 nm or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2020 / 179737 [Patent Document 2] Special Publication No. 2020-509190 [Patent Document 3] JP 2011-099129 A Summary of the Invention [Problem to be solved by the invention]

[0007] In Patent Document 1, it is taught that a total elongation of 13% or more can be achieved in relation to ductility, but there is no specific disclosure on the improvement of uniform elongation. Similarly, in Patent Document 1, in relation to punchability, it is specifically disclosed that the occurrence of cracks at the end face during punching is suppressed, but the improvement of fatigue properties at the punched end face is not necessarily fully considered. Therefore, the hot-rolled steel sheet described in Patent Document 1 still has room for improvement in terms of uniform elongation and punched end face fatigue properties.

[0008] Therefore, an object of the present invention is to provide a hot-rolled steel sheet having high strength and excellent uniform elongation and punched edge fatigue properties through a novel configuration. [Means for solving the problem]

[0009] In order to achieve the above object, the present inventors have investigated the chemical composition and microstructure of hot-rolled steel sheet. As a result, the present inventors have found that the strength of the steel sheet can be improved by utilizing precipitation strengthening by Cu, and that the uniform elongation can be improved by increasing the fraction of pearlite, which has a relatively high work hardening capacity among the microstructures, by appropriately controlling the C and Cr contents in the steel sheet, while the fatigue properties of the punched end surface can be improved by forming the cementite in the pearlite into a layered (lamellar) shape, thereby completing the present invention.

[0010] The present invention, which has achieved the above object, is as follows. (1) Chemical composition, in mass%, C: 0.20-0.30%, Si: 0.01 to 2.00%, Mn: 0.50-3.00%, P: 0.100% or less, S: 0.0100% or less, Al: 0.005 to 3.000%, N: 0.0100% or less, O: 0.0100% or less, Cr: over 1.00 ~ 3.00%, Cu: over 1.00 to 3.00%, Ti: 0 to 0.10%, Nb: 0-0.10%, V: 0~0.10%, Ni: 0-2.00%, Mo: 0-1.00%, B: 0~0.0100%, Ca: 0 to 0.0050%, REM: 0 to 0.005%, and The balance is Fe and impurities. The microstructure, in terms of area ratio, Perlite: 70% or more, Ferrite: 0-30%, and Bainite: 0-30% In the pearlite, the cementite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is 10 μm2 Less than 10 per A hot-rolled steel sheet having a tensile strength of 900 MPa or more. (2) The chemical composition is, in mass%, Ti: 0.001 to 0.10%, Nb: 0.001 to 0.10%, V: 0.001 to 0.10%, Ni: 0.001 to 2.00%, Mo: 0.001 to 1.00%, B: 0.0001~0.0100%, Ca: 0.0001 to 0.0050%, and REM: 0.0001~0.005% The hot-rolled steel sheet according to the above (1), characterized in that it contains one or more selected from the group consisting of: (3) The hot-rolled steel sheet according to (1) or (2) above, characterized in that it has a sheet thickness of 1.0 to 6.0 mm. Effect of the Invention

[0011] According to the present invention, it is possible to obtain a hot-rolled steel sheet having a high strength of tensile strength of 900 MPa or more, and excellent uniform elongation and punched edge fatigue properties. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram of a test piece (unit of dimensions in the figure: mm) used to evaluate the punched end face fatigue properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Hot-rolled steel sheets> The hot-rolled steel sheet according to the embodiment of the present invention is Chemical composition, in mass%, C: 0.20-0.30%, Si: 0.01 to 2.00%, Mn: 0.50-3.00%, P: 0.100% or less, S: 0.0100% or less, Al: 0.005 to 3.000%, N: 0.0100% or less, O: 0.0100% or less, Cr: over 1.00 ~ 3.00%, Cu: over 1.00 to 3.00%, Ti: 0 to 0.10%, Nb: 0-0.10%, V: 0~0.10%, Ni: 0-2.00%, Mo: 0-1.00%, B: 0~0.0100%, Ca: 0 to 0.0050%, REM: 0 to 0.005%, and The balance is Fe and impurities. The microstructure, in terms of area ratio, Perlite: 70% or more, Ferrite: 0-30%, and Bainite: 0-30% In the pearlite, the cementite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is 10 μm 2 Less than 10 per It is characterized by a tensile strength of 900 MPa or more.

[0014] As mentioned above, there is a problem that the uniform elongation and punched end surface fatigue properties required for forming a member generally decrease with increasing strength. Therefore, the present inventors first focused on pearlite, which has the highest work hardening ability among the microstructures other than the retained austenite, and found that the uniform elongation can be significantly improved and the fatigue properties of the punched end surface can be improved by appropriately controlling the C and Cr contents in the steel sheet to make the pearlite 70% or more in area ratio, and further, if a residual structure exists, making it mainly composed of ferrite and / or bainite. More specifically, a relatively high C content is generally required to generate a large amount of pearlite. However, the present inventors found that by increasing the Cr content to more than 1.00%, the pearlite generation region can be expanded to the low carbon side, and as a result, a high pearlite fraction of 70% or more in area ratio can be achieved despite a relatively low C content of 0.20 to 0.30%. Furthermore, the inventors have found that in such hot-rolled steel sheet having a relatively low C content of 0.20 to 0.30% and a Cr content of more than 1.00% and a microstructure mainly composed of pearlite, the fatigue properties of the punched end surface can be improved by substantially eliminating martensite, which has high hardness and low toughness, and retained austenite that generates the martensite through deformation-induced transformation.

[0015] Next, the present inventors conducted a study focusing on the morphology of cementite in pearlite in order to further improve the fatigue properties of the punched end surface in such hot-rolled steel sheet having a relatively low C content of 0.20 to 0.30%, a Cr content of more than 1.00%, and pearlite of 70% or more in area ratio. In the case of a steel sheet containing a relatively large amount of pearlite, minute voids may be generated on the punched end surface starting from the cementite or the interface between the cementite and ferrite during punching of the steel sheet. These voids may cause a decrease in the fatigue properties of the punched end surface after punching. In response to this, the present inventors aimed to reduce the amount of coarse spheroidal cementite in pearlite, more specifically, to reduce the amount of cementite with a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 in pearlite to 10 μm.2 It was found that by limiting the number density to less than 10 per punch, it is possible to suppress the generation of voids during punching, and as a result, it is possible to significantly improve the fatigue properties at the punched end surface.

[0016] Without intending to be bound by any particular theory, it is believed that by making the cementite in pearlite have a more layered (more lamellar) form, in the region near the punched end surface when the steel sheet is punched, the strong stress applied in the punching process forms a structure in which the cementite lamellar structure is aligned in one direction along the punching direction. It is believed that due to the aligned structure in the punched end surface, the fatigue properties are significantly improved compared to the case of a conventional microstructure that does not contain such a pearlite structure. On the other hand, when pearlite contains a large amount of coarse and spherical cementite, that is, when the cementite with a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is present in an area of ​​10 μm, the lamellar structure of the cementite is aligned in one direction along the punching direction. 2 If they are present at a number density of 10 or more per square inch, it is believed that such an ordered structure cannot be formed at the punched end surface during punching, and as a result, the fatigue properties of the punched end surface are degraded.The present inventors have also found that in order to suppress the formation of such coarse spheroidal cementite in pearlite and promote the formation of lamellar cementite, it is important to ensure a sufficient amount of carbon for forming pearlite, and for this purpose, it is effective to limit the amounts of alloy elements that form carbides, more specifically, Ti, Nb and V, to 0.10% or less, respectively, to suppress the consumption of carbon in the steel by these alloy elements.

[0017] Ti, Nb and V are elements that generally contribute to improving the strength of steel sheets by carbide precipitation. On the other hand, the hot-rolled steel sheets according to the embodiments of the present invention contain only a relatively low content of 0.20 to 0.30% C, which is an element effective in improving the strength of steel sheets, as described above. Therefore, it is generally difficult to achieve high strength, specifically a tensile strength of 900 MPa or more, while suppressing the contents of these elements to a relatively low content. Therefore, the present inventors have found that, despite such a relatively low C content, by including Cu in an amount of more than 1.00% in the steel sheet, the strength of the steel sheet can be maintained at a high level by utilizing precipitation strengthening by Cu. By utilizing precipitation strengthening by Cu, it is possible not to utilize or to limit the utilization of strength improvement by carbide precipitation of Ti, Nb and V. As a result, it is possible to sufficiently secure the amount of carbon required to form the desired pearlite structure according to the embodiments of the present invention by suppressing the formation of carbides by Ti, Nb and V.

[0018] In summary, the inventors have achieved a hot-rolled steel sheet having a high strength of 900 MPa or more, as well as excellent uniform elongation and punched edge fatigue properties, by combining mainly the following four findings. The combination of these findings and the fact that it results in a hot-rolled steel sheet having high strength, uniform elongation and excellent punched edge fatigue properties were not previously known, and have now been revealed for the first time by the inventors. (i) Despite the relatively low C content of 0.20 to 0.30%, by including Cr in an amount of more than 1.00% in the steel sheet, a pearlite fraction of 70% or more in terms of area ratio can be achieved, and as a result, uniform elongation can be improved. (ii) The remaining structure is composed of ferrite and / or bainite, and the microstructure is substantially free of martensite and retained austenite that generates the martensite through deformation-induced transformation, thereby improving the fatigue properties of the punched end surface; (iii) The content of Ti, Nb and V is limited to suppress the formation of carbides due to these elements, thereby ensuring a sufficient amount of carbon to form pearlite structures containing lamellar cementite, and as a result, the formation of coarse spheroidal cementite in pearlite, i.e., cementite with a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0, is suppressed to 10 μm. 2 The number of punched edges is limited to less than 10 per punch, thereby improving the fatigue properties of the punched edge. (iv) By utilizing precipitation strengthening with Cu, the formation of carbides due to Ti, Nb, and V is suppressed, and the formation of pearlite structure in (iii) above is promoted, while a high tensile strength of 900 MPa or more can be achieved despite the relatively low C content of 0.20 to 0.30%.

[0019] Hereinafter, the hot-rolled steel sheet according to the embodiment of the present invention will be described in more detail. In the following description, the unit of content of each element, "%", means "mass%" unless otherwise specified. In addition, in this specification, "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit unless otherwise specified.

[0020] [C:0.20~0.30%] C is an essential element for ensuring the strength of hot-rolled steel sheet. In order to fully obtain such effects, the C content is set to 0.20% or more. The C content may be 0.21% or more, 0.22% or more, or 0.23% or more. On the other hand, excessive C content may deteriorate the weldability of the steel sheet. For this reason, the C content is set to 0.30% or less. The C content may be less than 0.30%, 0.29% or less, 0.28% or less, 0.27% or less, 0.26% or less, 0.25% or less, or 0.24% or less. In the embodiment of the present invention, since the C content is relatively low as described above, it is advantageous in terms of weldability, and it is possible to achieve excellent fatigue properties not only at the punched end surface of the steel sheet itself but also at the welded portion, for example.

[0021] [Si: 0.01-2.00%] Silicon is an element used for deoxidizing steel. To fully obtain such an effect, the silicon content is set to 0.01% or more. The silicon content may be 0.10% or more, 0.20% or more, 0.30% or more, or 0.50% or more. On the other hand, excessive silicon content may deteriorate the chemical conversion treatability and may deteriorate the punched edge fatigue properties of the steel sheet due to residual austenite in the microstructure of the steel sheet. For this reason, the silicon content is set to 2.00% or less. The silicon content may be 1.85% or less, 1.70% or less, 1.50% or less, or 1.40% or less.

[0022] [Mn: 0.50~3.00%] Mn is an effective element for delaying the phase transformation of steel and preventing the phase transformation from occurring during cooling. To fully obtain such an effect, the Mn content is set to 0.50% or more. The Mn content may be 0.60% or more, 0.80% or more, 1.00% or more, 1.30% or more, or 1.50% or more. On the other hand, if Mn is contained excessively, microsegregation or macrosegregation may occur easily, which may reduce the hole expandability. For this reason, the Mn content is set to 3.00% or less. The Mn content may be 2.80% or less, 2.70% or less, 2.50% or less, or 2.20% or less.

[0023] [P:0.100% or less] P is an element that is mixed in during the manufacturing process. The lower the P content, the better; if it is excessive, it may adversely affect formability and weldability, and may also reduce fatigue properties. For this reason, the P content is set to 0.100% or less. It is preferably 0.090% or less or 0.070% or less, and more preferably 0.050% or 0.040% or less. The P content may be 0%, but excessive reduction will lead to increased costs. For this reason, the P content may be 0.0001% or more, 0.0005% or more, 0.001% or more, or 0.005% or more.

[0024] [S:0.0100% or less] S may form MnS and act as a fracture origin, significantly reducing the hole expandability of the steel sheet. For this reason, the S content is set to 0.0100% or less. The S content is preferably 0.0090% or less, and more preferably 0.0085% or less or 0.0070% or less. The S content may be 0%, but excessive reduction will lead to increased costs. For this reason, the S content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, or 0.0020% or more.

[0025] [Al: 0.005~3.000%] Al is an element used for deoxidizing steel. To fully obtain such an effect, the Al content is set to 0.005% or more. The Al content may be 0.010% or more, 0.030% or more, 0.050% or more, 0.100% or more, or 0.300% or more. On the other hand, if Al is contained excessively, inclusions increase and the workability of the steel sheet may deteriorate. For this reason, the Al content is set to 3.000% or less. The Al content may be 2.800% or less, 2.500% or less, 2.000% or less, 1.800% or less, 1.500% or less, or 1.200% or less.

[0026] [N:0.0100% or less] N combines with Al in steel to form AlN, and the pinning effect inhibits the pearlite block diameter from increasing, thereby improving the toughness of the steel. However, if N is contained excessively, the effect saturates and may instead cause a decrease in toughness. For this reason, the N content is set to 0.0100% or less. The N content is preferably 0.0090% or less, 0.0080% or less, or 0.0070% or less. From this perspective, the N content may be 0%, but excessive reduction will lead to an increase in costs. For this reason, the N content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, or 0.0020% or more.

[0027] [O:0.0100% or less] O is an element that is mixed in during the manufacturing process. If O is contained in excess, coarse inclusions may form, reducing the toughness of the steel plate. Therefore, the O content is 0.0100% or less. The O content may be 0.0090% or less, 0.0080% or less, 0.0070% or less, or 0.0060% or less. The O content may be 0%, but excessive reduction will increase costs. Therefore, the O content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, or 0.0020% or more.

[0028] [Cr: over 1.00~3.00%] Cr is an element that contributes to improving the strength of steel sheets, and also has the effect of suppressing the spheroidization of cementite. Therefore, in order to reduce the number density of coarse spheroidal cementite in pearlite and suppress the generation of voids during punching, it is necessary to contain a certain amount of Cr. Furthermore, since Cr stabilizes cementite, the inclusion of Cr can expand the pearlite formation region to the low carbon content side. Therefore, by containing an appropriate amount of Cr, i.e., an amount exceeding 1.00%, it is possible to achieve a pearlite fraction of 70% or more even in the case of a relatively low C content. The Cr content may be 1.01% or more, 1.02% or more, 1.03% or more, 1.05% or more, 1.10% or more, 1.30% or more, 1.50% or more, or 1.70% or more. On the other hand, if Cr is excessively contained, pearlite transformation is delayed, and a relatively large amount of hard structures such as bainite and martensite is generated, which may make it difficult to achieve a pearlite fraction of 70% or more. Alternatively, if Cr is excessively contained, the uniform elongation may decrease with the improvement of the tensile strength. Therefore, the Cr content is set to 3.00% or less. The Cr content may be 2.80% or less, 2.70% or less, 2.50% or less, 2.20% or less, 2.00% or less, or 1.80% or less.

[0029] [Cu: over 1.00 to 3.00%] Cu is an element effective in improving strength by precipitation strengthening. Moreover, unlike Ti, Nb, and V, Cu can improve the strength of the steel sheet without forming carbides. Therefore, Cu does not consume the carbon required to form the desired pearlite structure in which coarse spheroidal cementite is reduced. Therefore, Cu is an extremely important element in achieving both strength improvement and punched end face fatigue properties. In order to fully obtain these effects, the Cu content is made to be more than 1.00%. The Cu content may be 1.01% or more, 1.02% or more, 1.03% or more, 1.05% or more, 1.10% or more, 1.20% or more, 1.30% or more, 1.50% or more, or 1.70% or more. On the other hand, if Cu is contained excessively, the increase in precipitates may cause microcracks to occur on the surface during hot processing. Therefore, the Cu content is made to be 3.00% or less. The Cu content may be up to 2.80%, up to 2.70%, up to 2.50%, up to 2.20%, up to 2.00% or up to 1.80%.

[0030] The basic chemical composition of the hot rolled steel sheet according to the embodiment of the present invention is as described above. Furthermore, the hot rolled steel sheet may contain at least one of the following optional elements in place of a part of the remaining Fe, if necessary. For example, the hot rolled steel sheet may contain at least one selected from the group consisting of Ti: 0-0.10%, Nb: 0-0.10%, V: 0-0.10%, Ni: 0-2.00%, and Mo: 0-1.00%. In addition, the hot rolled steel sheet may contain B: 0-0.0100%. In addition, the hot rolled steel sheet may contain at least one selected from the group consisting of Ca: 0-0.0050% and REM: 0-0.005%. These optional elements will be described in detail below.

[0031] [Ti: 0~0.10%] [Nb: 0~0.10%] [V:0~0.10%] Ti, Nb and V are elements that contribute to improving the strength of the steel sheet by carbide precipitation. The Ti, Nb and V contents may be 0%, but in order to obtain the above effect, one selected from these may be contained alone or two or more may be contained in combination as necessary. In order to obtain the above effect, the Ti, Nb and V contents are preferably 0.001% or more, and may be 0.01% or more, 0.02% or more, or 0.03% or more. On the other hand, if these elements are contained excessively, a large amount of carbides will be generated, consuming carbon necessary to form a desired pearlite structure in which coarse spheroidal cementite is reduced. As a result, the punched end face fatigue properties may be deteriorated. For this reason, the Ti, Ni and V contents are preferably 0.10% or less. The Ti, Ni and V contents may be 0.08% or less, 0.06% or less, or 0.05% or less, respectively.

[0032] [Ni:0~2.00%] Ni is an element that dissolves in steel and can increase strength without impairing toughness. The Ni content may be 0%, but in order to obtain the above effect, the Ni content is preferably 0.001% or more. The Ni content may be 0.01% or more, 0.10% or more, 0.20% or more, or 0.50% or more. On the other hand, Ni is an expensive element, and excessive addition leads to an increase in costs. Therefore, the Ni content is preferably 2.00% or less. The Ni content may be 1.70% or less, 1.50% or less, or 1.20% or less.

[0033] [Mo:0~1.00%] Mo is an element that increases the strength of steel. The Mo content may be 0%, but in order to obtain the above effect, the Mo content is preferably 0.001% or more. The Mo content may be 0.01% or more, 0.02% or more, or 0.03% or more. On the other hand, if Mo is contained excessively, toughness may decrease along with an increase in strength. Therefore, the Mo content is preferably 1.00% or less. The Mo content may be 0.80% or less, 0.50% or less, 0.30% or less, 0.10% or less, 0.08% or less, 0.06% or less, or 0.05% or less.

[0034] [B:0~0.0100%] B has the effect of segregating at grain boundaries and increasing grain boundary strength. The B content may be 0%, but in order to obtain the above effect, the B content is preferably 0.0001% or more. The B content may be 0.0003% or more, 0.0005% or more, or 0.0010% or more. On the other hand, even if B is contained excessively, the effect becomes saturated, and therefore the raw material cost increases. For this reason, the B content is preferably 0.0100% or less. The B content may be 0.0080% or less, 0.0060% or less, or 0.0050% or less.

[0035] [Ca: 0~0.0050%] Ca is an element that controls the form of nonmetallic inclusions that become the starting point of fracture and cause deterioration of workability, and improves workability. The Ca content may be 0%, but in order to obtain the above effect, the Ca content is preferably 0.0001% or more. The Ca content may be 0.0003% or more, 0.0005% or more, or 0.0010% or more. On the other hand, even if Ca is contained excessively, the effect becomes saturated, and therefore the raw material cost increases. For this reason, the Ca content is preferably 0.0050% or less. The Ca content may be 0.0045% or less, or 0.0040% or less.

[0036] [REM:0~0.005%] REM is an element that improves the toughness of a welded portion by adding a small amount. The REM content may be 0%, but in order to obtain the above effect, the REM content is preferably 0.0001% or more. The REM content may be 0.0003% or more, 0.0005% or more, or 0.001% or more. On the other hand, excessive REM content may cause a decrease in weldability. For this reason, the REM content is preferably 0.005% or less. The REM content may be 0.004% or less, or 0.003% or less. In this specification, REM is a collective term for 17 elements, namely, scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content is the total content of these elements.

[0037] In the hot-rolled steel sheet according to the embodiment of the present invention, the balance other than the above elements is composed of Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the hot-rolled steel sheet is industrially manufactured. Examples of the impurities include Sn: 0.02% or less, Sb: 0.02% or less, W: 0.015% or less, and Co: 0.015% or less.

[0038] [Perlite: 70% or more] The microstructure of the hot-rolled steel sheet contains 70% or more of pearlite in terms of area ratio. Since pearlite has the highest work hardening ability among microstructures other than retained austenite, by making the microstructure of the hot-rolled steel sheet a structure mainly composed of pearlite, it is possible to obtain a steel sheet with excellent uniform elongation while maintaining high strength. For example, if ferrite is generated excessively and the area ratio of pearlite is less than 70% as a result, it may not be possible to ensure sufficient strength. On the other hand, if bainite is generated excessively and the area ratio of pearlite is less than 70% as a result, the strength is improved but the uniform elongation may be reduced. For this reason, the area ratio of pearlite is set to 70% or more, and may be 72% or more, 75% or more, 77% or more, 80% or more, 85% or more, or 90% or more. The upper limit of the area ratio of pearlite is not particularly limited and may be 100%. For example, the area ratio of pearlite may be 99% or less, 98% or less, 96% or less, 94% or less, 92% or less, 90% or less, 87% or less, 83% or less, or 79% or less.

[0039] [Ferrite: 0~30%] [Bainite: 0~30%] The remaining structure other than pearlite may be 0% in area ratio, but if the remaining structure exists, it is composed of at least one of ferrite and bainite. Therefore, the area ratio of ferrite and bainite is 0 to 30%. The area ratio of ferrite and bainite may be 1% or more, 2% or more, 4% or more, or 6% or more, respectively. Similarly, the area ratio of ferrite and bainite may be 25% or less, 20% or less, 15% or less, or 10% or less, respectively. By forming the remaining structure from ferrite and / or bainite, that is, by not having or substantially not having high hardness and low toughness martensite in the remaining structure, or by not having retained austenite that generates the martensite by processing induced transformation in the remaining structure, it is possible to ensure good punched edge fatigue properties. In this specification, the expressions "substantially not present" or "substantially not included" mean that the area ratio of martensite and retained austenite in the remaining structure is less than 0.5% in total. Since it is difficult to accurately measure the total amount of such minute structures, and the influence of such structures can be ignored, it is possible to determine that these structures do not exist when the total amount of these structures is less than 0.5%. The total of the area ratio of ferrite and the area ratio of bainite may be 30% or less, 25% or less, 21% or less, 17% or less, 13% or less, 10% or less, 8% or less, 6% or less, 4% or less, 2% or less, or 1% or less, or may be 0%. On the other hand, the total of the area ratio of ferrite and the area ratio of bainite may be 1% or more, 2% or more, 4% or more, 6% or more, 8% or more, 10% or more, 13% or more, 17% or more, or 21% or more, as necessary.

[0040] [Number density of cementite in pearlite with a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0: 10 μm 2 Less than 10 per In an embodiment of the present invention, the number density of coarse spheroidal cementite among the cementite constituting pearlite is limited within a predetermined range, and more specifically, the number of cementite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 in pearlite is limited to 10 μm.2 The aspect ratio of cementite is less than 10 per 100 μm. The aspect ratio of cementite refers to the value obtained by dividing the length of the major axis of cementite appearing on the observation surface by the length of the minor axis. In this specification, cementite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is defined as coarse spheroidal cementite. Such coarse spheroidal cementite may become the starting point of void generation during punching of a steel plate, and these voids may cause a decrease in fatigue properties at the punched end surface after punching. Therefore, in order to improve the fatigue properties at the punched end surface, it is extremely important to reduce the amount of such coarse spheroidal cementite. In this regard, in an embodiment of the present invention, the number density of the above-mentioned coarse spheroidal cementite is set to 10 μm. 2 The number density of coarse spheroidal cementite is limited to less than 10 per square meter, which reliably suppresses the generation of voids during punching, and as a result, it is possible to significantly improve the fatigue properties at the punched end surface. 2 The number density of the coarse spheroidal cementite may be 8 or less, 6 or less, or 4 or less per grain. 2 The number of cementite particles per grain may be 0, or may be, for example, 1 or more, or 2 or more. Although details will be described later, the aspect ratio refers to the ratio of the length of the major axis to the length of the minor axis of an ellipsoid when an ellipsoid approximation process is performed on each cementite particle by image processing.

[0041] [Method for measuring area ratio of microstructure] The area ratio of the microstructure is determined as follows. First, a sample is taken from a position 1 / 4 or 3 / 4 of the way down from the surface of the steel plate so that the cross section parallel to the rolling direction and thickness direction of the steel plate becomes the observation surface. Next, the observation surface is mirror-polished and etched with a picral etching solution, after which the structure is observed using a scanning electron microscope (SEM). The measurement area is 12,000 μm 2The area of ​​the sample is set to 80 μm×150 μm (for example, 80 μm×150 μm), and the area ratios of pearlite and ferrite are calculated from a micrograph with a magnification of, for example, about 5000 times by using a point counting method. Here, a region surrounded by grain boundaries where the crystal orientation difference of ferrite is 15° or more, where the ferrite phase and the cementite phase are mixed, and where the cementite is in a layered and / or spherical form, is recognized as pearlite. Therefore, for example, pearlite includes not only a structure in which the ferrite phase and the cementite are dispersed in a layered (lamellar) form, but also a structure mainly composed of cementite dispersed in a block form, more specifically, a structure containing such a block form of cementite at an area ratio of more than 50% of the total amount of cementite in the structure. Also, a collection of lath-shaped crystal grains, which has a plurality of iron-based carbides with a major axis of 20 nm or more inside the lath, and further, which belong to a single variant, i.e., a group of iron-based carbides elongated in the same direction, is recognized as bainite. Inclusions observed in pearlite structures are basically cementite, and there is no need to identify each inclusion as cementite or iron-based carbide using a scanning electron microscope with an energy dispersive X-ray spectrometer (SEM-EDS) or the like. Only when there is any doubt as to whether the inclusion is cementite or iron-based carbide, if necessary, can the inclusion be analyzed using SEM-EDS or the like in addition to SEM observation. Retained austenite has an internal cementite area fraction of less than 1%, and if such a structure is found, it is analyzed using electron backscatter diffraction (EBSD) after SEM structure observation, and the fcc structure is determined to be retained austenite.

[0042] [Method for measuring the number density of cementite in pearlite with a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0] The number density of coarse spheroidal cementite is determined as follows. First, a sample is taken from a position 1 / 4 or 3 / 4 of the way down from the surface of the steel plate to the plate thickness, so that the cross section parallel to the rolling direction and thickness direction of the steel plate becomes the observation surface. Next, the observation surface is mirror-polished and etched with a picral etching solution, after which the structure is observed using a scanning electron microscope (SEM). The measurement area is 12,000 μm 2 In an SEM photograph of a region recognized as pearlite at a magnification of about 5000 times (for example, an area of ​​80 μm × 150 μm), an image of the region recognized as pearlite is binarized, and the dark areas are regarded as ferrite and the light areas as cementite. Of these, each cementite is approximated to an ellipsoid by image processing, and the lengths of the major axis and minor axis of the ellipsoid are defined as the lengths of the major axis and minor axis of each cementite, respectively, and the aspect ratio of each cementite is defined by the following formula. [Aspect ratio] = [Length of major axis] / [Length of minor axis] The number of cementite particles in a visual field of 80 μm × 150 μm that have a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 as defined above was calculated by image processing, and this was divided into 10 μm 2 The value converted into per unit area is determined as the number density of the coarse spheroidal cementite defined in the present invention.

[0043] [Mechanical properties] According to the hot-rolled steel sheet having the above chemical composition and structure, high tensile strength, specifically tensile strength of 900 MPa or more can be achieved. The tensile strength is preferably 910 MPa or more or 920 MPa or more, more preferably 940 MPa or more or 980 MPa or more, and most preferably 1000 MPa or more or 1080 MPa or more. There is no need to specify the upper limit, but for example, the tensile strength may be 1500 MPa or less or 1400 MPa or less. Similarly, according to the hot-rolled steel sheet having the above chemical composition and structure, high uniform elongation can be achieved, more specifically, a uniform elongation of 7.0% or more, preferably 7.5% or more, more preferably 8.0% or more can be achieved. There is no need to specify the upper limit, but for example, the uniform elongation may be 20.0% or less or 15.0% or less. Tensile strength and uniform elongation are measured by taking JIS Z2241:2011 No. 5 tensile test pieces from the direction perpendicular to the rolling direction of hot-rolled steel sheets and conducting tensile tests in accordance with JIS Z2241:2011. Uniform elongation refers to the plastic elongation (%) at the maximum test force specified in JIS Z2241:2011.

[0044] Similarly, the hot-rolled steel sheet having the above-mentioned chemical composition and structure can achieve high punched edge fatigue properties. More specifically, the fatigue limit σ F (MPa) divided by tensile strength TS (MPa) (σ FA punched end face fatigue characteristic of 0.28 or more can be achieved at a punching fatigue limit ratio corresponding to the end face fatigue characteristic (T / TS). The punching fatigue limit ratio is preferably 0.30 or more, more preferably 0.32 or more. There is no particular need to specify the upper limit value, but for example, the punching fatigue limit ratio may be 0.42 or less or 0.40 or less. The punching fatigue limit ratio is determined by the following method using a plate-shaped test piece having the dimensions shown in FIG. 1. First, a punched hole is made at the center of a plate-shaped test piece (30 mm x 90 mm) taken from a hot-rolled steel sheet with the rolling direction as the long side, with a punch diameter of 10 mm and a punching clearance of 12%, and then a reverse plane bending fatigue test is performed at a constant stress amplitude σ (MPa). In order to prevent cracks from occurring from the end face corners of the plate-shaped test piece, the end face corners of the plate may be R-chamfered as shown in FIG. 1. When the number of repetitions N is 10 7 The reversed plane bending fatigue test was performed until the maximum stress amplitude reached 1000 times, and the maximum stress amplitude among the tests that did not result in fracture was defined as the fatigue limit σ F (MPa), and the fatigue limit σ F (MPa) divided by tensile strength TS (MPa) (σ F / TS) is determined as the punching fatigue limit ratio.

[0045] Plate Thickness The hot rolled steel sheet according to the embodiment of the present invention generally has a sheet thickness of 1.0 to 6.0 mm. Although not particularly limited, the sheet thickness may be 1.2 mm or more, 1.6 mm or more, or 2.0 mm or more, and / or 5.0 mm or less, 4.0 mm or less, or 3.0 mm or less.

[0046] <Manufacturing method of hot-rolled steel sheet> Next, a preferred method for manufacturing the hot-rolled steel sheet according to the embodiment of the present invention will be described. The following description is intended to exemplify a characteristic method for manufacturing the hot-rolled steel sheet according to the embodiment of the present invention, and is not intended to limit the hot-rolled steel sheet to one manufactured by the manufacturing method described below.

[0047] A preferred method for producing a hot-rolled steel sheet according to an embodiment of the present invention includes the steps of: heating a slab having the chemical composition described above in relation to hot rolled steel sheet to above 1150°C; A hot rolling process including finish rolling a heated slab, wherein the delivery temperature of the finish rolling is 820 to 920°C; a cooling step including primarily cooling the obtained steel sheet from the finish rolling delivery temperature to a primary cooling end temperature of 720°C or less at an average cooling rate of 50°C / sec or more, and then secondary cooling to a coiling temperature at an average cooling rate of 10°C / sec or less; A step of coiling the steel sheet at a coiling temperature of 580 to 650°C; and An additional cooling step including cooling the coiled steel sheet to a steel sheet temperature of 550°C or less, in which the time required for the steel sheet temperature to reach 550°C after coiling is 30 to 180 minutes. Each step will be described in detail below.

[0048] [Slab heating process] First, a slab having the chemical composition described above in relation to the hot-rolled steel sheet is heated before hot rolling. The heating temperature of the slab is 1150°C or higher in order to sufficiently redissolve Ti carbonitrides and the like. The upper limit is not particularly specified, but may be, for example, 1250°C. The heating time is not particularly limited, but may be, for example, 30 minutes or more and / or 120 minutes or less. The slab used is preferably cast by a continuous casting method from the viewpoint of productivity, but may also be produced by an ingot casting method or a thin slab casting method.

[0049] [Hot rolling process] (rough rolling) In this method, for example, the heated slab may be subjected to rough rolling before finish rolling in order to adjust the plate thickness, etc. The conditions of the rough rolling are not particularly limited as long as the desired sheet bar dimensions can be secured.

[0050] (Finish rolling) The heated slab or the slab that has been rough-rolled as necessary is then subjected to finish rolling, and the exit temperature in the finish rolling is controlled to 820 to 920 ° C. If the exit temperature of the finish rolling exceeds 920 ° C, the accumulation of processing strain in austenite during cooling is insufficient, pearlite transformation is delayed, and a pearlite fraction of 70% or more cannot be achieved. For this reason, the upper limit of the exit temperature of the finish rolling is set to 920 ° C, preferably 915 ° C, and more preferably 910 ° C. From this point of view, there is no need to set a lower limit on the exit temperature of the finish rolling as long as it is at or above the Ar3 point, but the lower the temperature, the greater the deformation resistance of the steel sheet, which puts a great burden on the rolling machine and may cause equipment trouble. For this reason, the lower limit of the exit temperature of the finish rolling is set to 820 ° C.

[0051] [Cooling process] After finish rolling, the steel plate is cooled. The cooling process is further divided into primary cooling and secondary cooling.

[0052] (Primary cooling: Cool down to 720℃ or less at 50℃ / sec or more) In the cooling step, the steel sheet is first primarily cooled from the finish rolling exit temperature to a primary cooling end temperature of 720°C or less at an average cooling rate of 50°C / sec or more. If the average cooling rate to the primary cooling end temperature is less than 50°C / sec or if the primary cooling end temperature exceeds 720°C, a large amount of ferrite is generated, making it impossible to achieve a pearlite fraction of 70% or more. The average cooling rate of the primary cooling may be 52°C / sec or more. There is no particular upper limit to the average cooling rate, but for example, the average cooling rate of the primary cooling is preferably 200°C / sec or less in order to obtain a desired structure, and may be 100°C / sec or less.

[0053] (Secondary cooling: Cool down to winding temperature at 10℃ / sec or less) Subsequently, in the secondary cooling, the steel sheet is cooled from the primary cooling end temperature to the coiling temperature (i.e., a temperature range of 580 to 650°C) at an average cooling rate of 10°C / sec or less. If the average cooling rate of the secondary cooling is higher than 10°C, temperature unevenness is likely to occur in the thickness direction and width direction of the steel sheet, resulting in variation in the metal structure. By setting the average cooling rate of the secondary cooling to 10°C / sec or less, it is possible to reliably reduce such variation in the metal structure in the thickness direction and width direction of the steel sheet. The average cooling rate of the secondary cooling is preferably 9°C / sec or less. Although the lower limit of the average cooling rate is not particularly limited, from the viewpoint of productivity, the average cooling rate of the secondary cooling is 1°C / sec or more, and may be 2°C / sec or more. It is preferable to perform the secondary cooling immediately after the end of the primary cooling in order to reliably obtain the effect of dividing the cooling process into two stages.

[0054] [Winding process] After the cooling step, the steel sheet is coiled. The temperature of the steel sheet during coiling is 580 to 650°C. If the coiling temperature is less than 580°C, a large amount of bainite is generated, and it becomes impossible to achieve a pearlite fraction of 70% or more. On the other hand, if the coiling temperature exceeds 650°C, the precipitated Cu particles become coarse, and sufficient precipitation strengthening ability by Cu cannot be obtained, and as a result, a tensile strength of 900 MPa or more cannot be achieved. Alternatively, ferrite is excessively generated, and sufficient tensile strength cannot be achieved. By controlling the coiling temperature to 580 to 650°C, it becomes possible to achieve a pearlite fraction of 70% or more while making the Cu particles precipitated with such pearlite transformation fine. Therefore, it is possible to fully exert the precipitation strengthening effect by Cu, and as a result, it is possible to significantly improve the strength of the steel sheet, and more specifically, to achieve a tensile strength of 900 MPa or more. The coiling temperature may be 584°C or more and / or 640°C or less.

[0055] [Additional cooling process: Time required to reach 550℃ after winding is 30 to 180 minutes] In the present manufacturing method, an additional cooling step is carried out after the coiling step, that is, a cooling step after coiling, in which the steel sheet is cooled from the coiling temperature to a steel sheet temperature of 550°C or less. During this cooling, it is important to control the time until the steel sheet temperature reaches 550°C after coiling within a range of 30 to 180 minutes. If the time until the steel sheet temperature reaches 550°C is less than 30 minutes, a large amount of bainite is generated and pearlite is not generated sufficiently, making it impossible to achieve a pearlite fraction of 70% or more. On the other hand, if this time exceeds 180 minutes, the cementite in the generated pearlite becomes coarse and spheroidized. In this case, the number density of cementite in pearlite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is controlled to 10 μm. 2 It becomes impossible to limit the number of voids to less than 10 per one piece, and the occurrence of voids cannot be sufficiently suppressed during punching of the steel sheet. On the other hand, by controlling the cooling time until the steel sheet temperature reaches 550°C within a range of 30 to 180 minutes after the coiling process is appropriately performed as described above, it becomes possible to obtain a desired pearlite structure in which coarse spheroidal cementite is reduced while reliably achieving a pearlite fraction of 70% or more. As a result, it is possible to reliably suppress the occurrence of voids during punching, and to significantly improve the fatigue properties at the punched end surface. For example, the time until the steel sheet temperature reaches 550°C may be 35 minutes or more and / or 150 minutes or less. The time until the steel sheet temperature reaches 550°C can be adjusted by any appropriate method. For example, when the coiling temperature is around 580°C, the coiled coil may be covered with a heat-insulating cover or the like as necessary to ensure that the steel sheet temperature reaches 550°C for 30 minutes or more.

[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES

[0057] In the following examples, hot-rolled steel sheets according to the embodiments of the present invention were produced under various conditions, and the mechanical properties of the obtained hot-rolled steel sheets were examined.

[0058] First, slabs having the chemical composition shown in Table 1 were produced by a continuous casting method. Next, hot-rolled steel sheets with a thickness of 2.5 mm were produced from these slabs by the heating, hot rolling, cooling, coiling and additional cooling conditions shown in Table 2. The balance other than the components shown in Table 1 is Fe and impurities. In addition, the chemical composition of a sample taken from the produced hot-rolled steel sheet was analyzed and found to be equivalent to the chemical composition of the slabs shown in Table 1, and in particular, the Sn and Sb contents in the impurities were 0.02% or less, and the W and Co contents were 0.015% or less.

[0059] [Table 1]

[0060] [Table 2]

[0061] From the hot-rolled steel sheet thus obtained, tensile test pieces of JIS Z2241:2011 No. 5 were taken from the direction perpendicular to the rolling direction, and tensile tests were conducted in accordance with JIS Z2241:2011 to measure the tensile strength (TS) and uniform elongation (uEl). The punched end fatigue properties were evaluated by the following method using plate-shaped test pieces with the dimensions shown in Figure 1. First, a punched hole was made in the center of the plate-shaped test piece (30 mm x 90 mm) taken from the hot-rolled steel sheet with the rolling direction as the long side, with a punch diameter of 10 mm and a punching clearance of 12%, and then a reverse plane bending fatigue test was conducted at a constant stress amplitude σ (MPa). In order to prevent cracks from occurring from the corners of the plate end surface of the plate-shaped test piece, the corners of the plate end surface may be chamfered as shown in Figure 1. When the number of repetitions N was 10 7 The reversed plane bending fatigue test was performed until the maximum stress amplitude reached 1000 times, and the maximum stress amplitude among the tests that did not result in fracture was defined as the fatigue limit σ F (MPa), and the fatigue limit σ F(MPa) divided by tensile strength TS (MPa) (σ F / TS) was determined as the punching fatigue limit ratio. Hot-rolled steel sheets with TS of 900 MPa or more, uEl of 7.0% or more, and punching fatigue limit ratio of 0.28 or more were evaluated as having high strength, uniform elongation, and excellent punching edge fatigue properties. The results are shown in Table 3 below.

[0062] [Table 3]

[0063] Referring to Table 3, in Comparative Example 9, since the average cooling rate of the first cooling in the cooling process was low, a large amount of ferrite was generated, and it was not possible to achieve a pearlite fraction of 70% or more. As a result, TS decreased. In Comparative Example 10, since the cooling end temperature of the first cooling was high, a large amount of ferrite was generated similarly, and it was not possible to achieve a pearlite fraction of 70% or more. As a result, TS decreased. In Comparative Example 11, since the coiling temperature was low, a large amount of bainite was generated, and it was not possible to achieve a pearlite fraction of 70% or more. As a result, TS improved, but uEl decreased. In Comparative Example 12, since the coiling temperature was high, a large amount of ferrite was generated, and it was not possible to achieve a pearlite fraction of 70% or more. In addition, in Comparative Example 12, since the coiling temperature was high, it is considered that the precipitated Cu particles became coarse, and the precipitation strengthening ability of Cu was not fully exhibited. As a result, TS decreased. In Comparative Example 13, since the time until the temperature reached 550 ° C after coiling was short, a large amount of bainite was generated, and although TS improved, uEl decreased. In Comparative Example 14, since the time until the temperature reached 550 ° C after coiling was long, the cementite in the pearlite became coarse and spheroidized, and the number density of such coarse spheroidal cementite could not be reduced. As a result, the punching fatigue limit ratio decreased. In Comparative Examples 19 and 20, since the C and Cr contents were low, pearlite was not generated sufficiently, while a large amount of ferrite was generated, and as a result, TS decreased. In Comparative Example 21, since the Cr content was high, strength was improved, but uEl decreased accordingly. In Comparative Example 22, since the Cu content was low, the precipitation strengthening ability of Cu was not fully exhibited, and TS decreased. In Comparative Examples 24, 26, and 28, since the Ti, Nb, and V contents were high, respectively, the generation of coarse spheroidal cementite could not be sufficiently reduced, and the punching fatigue limit ratio decreased. This result is believed to be due to the fact that the excess Ti, Nb and V produced a large amount of carbides, consuming the carbon necessary to form the desired pearlite structure with reduced coarse spheroidal cementite.

[0064] In contrast, in Examples 1 to 8, 15 to 18, 23, 25, 27, and 29 to 36, by having a predetermined chemical composition and microstructure, and further reducing the amount of coarse spheroidal cementite in pearlite in the microstructure, it was possible to achieve a uEl of 7.0% or more and a punching fatigue limit ratio of 0.28 or more, despite the high strength of TS of 900 MPa or more, and therefore it was possible to obtain hot-rolled steel sheets with high strength, uniform elongation, and excellent punching end fatigue properties. In addition, similar fatigue tests were performed on test pieces from welded members obtained by arc welding the steel sheets of each Example. As a result, in all Examples, it was possible to achieve high fatigue properties equivalent to those in the case of not including such a welded portion. It is believed that this is mainly due to the relatively low C content of 0.30% or less.

Claims

1. The chemical composition, in mass%, is C: 0.20-0.30%, Si: 0.01-2.00%, Mn: 0.50-3.00%, P: 0.100% or less, S: 0.0100% or less, Al: 0.005-3.000%, N: 0.0100% or less, O: 0.0100% or less, Cr: more than 1.00 to 3.00%, Cu: more than 1.00 to 3.00%, Ti: 0 to 0.10%, Nb: 0 to 0.10%, V: 0-0.10%, Ni: 0-2.00%, Mo: 0-1.00%, B: 0 to 0.0100%, Ca: 0-0.0050%, REM: 0 to 0.005%, and The balance is Fe and impurities. The microstructure, in terms of area ratio, Perlite: 70% or more, Ferrite: 0-30%, and Bainite: 0-30% In the pearlite, the cementite having a major axis length of more than 0.3 μm and an aspect ratio of less than 3.0 is 10 μm 2 less than 10 per A hot-rolled steel sheet having a tensile strength of 900 MPa or more.

2. The chemical composition, in mass%, Ti: 0.001 to 0.10%, Nb: 0.001 to 0.10%, V: 0.001-0.10%, Ni: 0.001 to 2.00%, Mo: 0.001-1.00%, B: 0.0001 to 0.0100%, Ca: 0.0001 to 0.0050%, and REM: 0.0001-0.005% The hot-rolled steel sheet according to claim 1, comprising one or more selected from the group consisting of:

3. The hot rolled steel sheet according to claim 1 or 2, characterized in that it has a sheet thickness of 1.0 to 6.0 mm.

Citation Information

Patent Citations

  • HIGH-STRENGTH STEEL SHEET HAVING TENSILE STRENGTH OF 1,500 MPa OR MORE, AND METHOD FOR MANUFACTURING THE SAME

    JP2011099129A

  • High-carbon hot-rolled steel sheet with excellent material uniformity and method for manufacturing the same

    JP2015515548A

  • High-strength steel sheet with excellent high-temperature elongation properties, warm press-formed member, and manufacturing method thereof

    JP2020509190A

  • High carbon hot / cold rolled steel coil and manufactureing method thereof

    KR1020130068403A

  • Hot-rolled steel sheet and production method therefor

    WO2020179737A1